PARTISIPASI POLITISI MILENIAL: STUDI KASUS PENCALONAN DODOK SAMDANA SUKAJA DAN I GEDE WEGA PRASTAMA SEBAGAI CALEG PADA PEMILU LEGISLATIF TAHUN 2019 - Arlyta, Sevira Astrelia; Erawan, Drs. I Ketut Putra; Mahaswari J.M, A.A.Sagung Mirah (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
The "Battle" of Legislative Election in Indonesia is mostly dominated by elder and mature participants. Nevertheless does not rule out the possibility of younger and millennial participants. The participation of millennial participants in the arena of practical politics brings out an obstacle such as lack of experience and some of them took a mistaken strategy in their political career. Owning in network resources or relationships could affect the final result of their election. This research uses Rational Choice theory. Data found that millennial politician (Dodok Samdana Sukaja & I Gede Wega Prastama) has not succeeded 2019 Indonesian Legislative Election. It occurs because one of them took a mistaken strategy . Consequently, both two millennial politicians achieve the suboptimal outcome. Based on these findings, the suboptimal outcome achieved by both millennial politicians provides a benefit in building a wider political relationship, developing branding in their society, and comprehending the political arena.